The Implementation of Music in Teaching Persian Heritage Speaking Students in International Schools: The Case of Persian Students in Dubai - Faroughi, Fatemeh; Dabney-Fekete, Ilona; Hajian, Foroozan (Central European Journal of Educational Research, 2025)
It is widely acknowledged that music plays an important role in education as a powerful tool for identity formation. Within the educational sphere, there is limited empirical evidence to show how heritage language learners do engage with music as a resource for learning and to maintain linguistic knowledge. This research is a step towards achieving a deeper understanding of how Persian students residing in the United Arab Emirates connect with their mother tongue in the multicultural society of the country. The aim is to investigate whether integration of music into the Persian literature classroom of the International Baccalaureate Diploma Programme can enhance the students’ comprehension and cultural understanding among Persian students. Therefore, the study addresses three central questions: (1) Does using music in the classroom improve students’ understanding of classic Persian literature? (2) How does using music affect their motivation and emotional engagement if used in the classroom? (3) What impact does using music have on students staying connected to their heritage language and culture? This study was conducted in 2023 in the UAE and using a two-phase within-subject design. There were twelve IBDP students between 16 to 19 years old participating in the research answering questionnaires after reading ghazals by Rumi and again after listening to the musical adaptations of the same poems. A Google Form was used to analyse the data through descriptive statistics and thematic coding. Findings show that listening to music significantly improved understanding Persian poetry and detecting literary devices and comprehension was easier.